487 Clinical Outcomes of Decompressive Spine Surgery for Painless Cervical Myelopathy: An Analysis of the Michigan Spine Surgery Improvement Collaborative (MSSIC) Registry. (April 2023) - Deshpande, Nachiket; Fadel, Hassan Ali; Schultz, Lonni; Abdulhak, Muwaffak; Chang, Victor W.; Schwalb, Jason M.
Abstract : INTRODUCTION: Cervical myelopathy (CM) is the occurrence of neurologic dysfunction secondary to any etiology that results in direct cervical spinal cord compression. Although axial neck pain and radicular arm pain are common presenting features in CM, some patients present atypically with myelopathic symptoms in the absence of neck or arm pain. To date, little is known regarding the outcomes of surgical decompression in these patients. METHODS: This is a retrospective study of prospectively collected data from the Michigan Spine Surgery Improvement Collaborative (MSSIC) registry. A total of 340 patients undergoing spine surgery for painless CM were analyzed. Surgical and patient reported outcomes, including minimal clinically important difference (MCID) in modified Japanese Orthopedic Association (mJOA) scores and Patient-Reported Outcomes Measurement Information System Physical Function (PROMIS PF) scores, were assessed at 90 days, 1 year, and 2 years postoperatively. RESULTS: At 90 days following surgery, a MCID in PROMIS PF and mJOA scores was seen in 42% and 36% of patients, respectively. The proportion of patients with MCID in mJOA scores remained stable at 1- and 2-year follow-up, while the percentage of patients with MCID in PROMIS PF scores decreased to 22% at two years post-operatively. When stratifying by pre-operative CM severity, patient reported outcomes and surgical complications did not significantly vary. Importantly, patient satisfaction remained above 80% at 90 days, 1 year, and 2 years after surgery. CONCLUSIONS: Following surgical intervention, clinically significant improvement was seen in a modest number of patients. The high degree of sustained patient satisfaction suggests that our measured outcomes may not accurately capture the degree of improvement that is important to patients, or it may represent happiness from not experiencing further functional decline.